ANALISIS PELAKSANAAN PENGELOLAAN SANITASI LAUNDRY (LINEN) DI RUMAH SAKIT UMUM MARTHA FRISKA MEDAN TAHUN 2014 - Suriani Gultom; indra chahaya; taufik ashar (Lingkungan dan Kesehatan Kerja, 2014)
Sanitation management of the linen is one special sanitation efforts at the hospital because it has sharp attention on the activities or processes because of its distinctive properties and can cause hazard/risk high for officers, hospital visitors and patients. Many of the problems that will probably arise from nosocomial infections, among others, when health workers who suffer from infections due to certain pathogenic microorganisms, it is because the health care personnel with direct patient contact, because linen is the object that engaged directly with patients and the management of the linen is not good will give negative impact to the hospital The present study  is  a descriptive survey with the object  includes  the operation of sanitation linen of  Martha Friska Hospital Medan and 10persons  of  loundry as the respondent by using direct observation for the  object of the study and  direct interview  with the informant. The objective of the study  is to know the  facility and infrastructure of  laundry sanitation, characteristics  (age, duration of service on job,  education level,  participation in  training and  knowledge)  and  analysis of  the solid  waste treatment of  Martha Friska hospital  Medan in 2014. The result of the study  showed that the score of all variables is of 70%. It  indicates that  in fact, the operation of  laundry sanitation of Martha Friska hospital Medan was still not adjusted to the requirements of  laundry sanitation according to Kepmenkes RI  with the minimal standard of ≥ 80%. The conclusion of the study is that  the operation of the solid waste treatment  of hospital is still not adjusted to the Kepmenkes RI , including the inadequate facility and infrastructure. For that reason,  it is  expected that  all the laundry installation of Martha Friska hospital to more increase in  the supportive facility by supplying the more  complete facility and infrastructure to the laundry  that they use  the complete self-protective tool Keywords: Analysis, Operation, Treatment, Sanitation, loundry